2016
DOI: 10.1016/j.comptc.2016.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio multi-reference perturbation theory calculations of the ground and low-lying electronic states of the KRb molecule

Abstract: The potential energy curves of the low-lying electronic states correlating up to the limit K(4p) + Rb(5s) of KRb molecule have been calculated using the multi-reference perturbation theory method at the CASSCF/ XMCQDPT2 level of theory without and with spin-orbit coupling. The calculated parameters of the ground X 1 R + state are in the best agreement among all previously performed ab initio calculations for the KRb molecule. The calculated vibrational intervals of the ground electronic term of the 39 K 85 Rb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…The first three excited configurations, atomic states, and their energies of the Rb atom are: 5p ? 2 P 1/2 (12,578.950 cm À1 ), 2 (20,132.510 cm À1 ) [15]. The SOC splittings of the 2 P and 2 D terms are 237.595 and 0.446 cm À1 , respectively.…”
Section: Computationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first three excited configurations, atomic states, and their energies of the Rb atom are: 5p ? 2 P 1/2 (12,578.950 cm À1 ), 2 (20,132.510 cm À1 ) [15]. The SOC splittings of the 2 P and 2 D terms are 237.595 and 0.446 cm À1 , respectively.…”
Section: Computationsmentioning
confidence: 99%
“…So, the following parameters of the ab initio calculations at the MRPT + SOC level of theory influence the calculation accuracy: a number of the states considered in the perturbation theory method [12] (i); qualitative composition (R, P, D) of the above-mentioned states [12] (ii); the energy denominator shift (EDS) for the intruder state avoidance (ISA) [12,18] (iii), and Z eff values [21] (iv). These parameters allow one to vary the energies of the low-lying atomic states, and the optimal choice of these parameters provides the required accuracy for the characteristics of the low-lying electronic molecular states.…”
Section: Computationsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 A new approach to the MS-MR-PT (Multi-State Multi-Reference Perturbation Theory) level of theory, which is called XMCQDPT (Extended Multi-Configuration Quasi-Degenerate Perturbation Theory), which is free from some disadvantages of the earlier versions of the MS-MR-PT, has been developed by Granovsky. 32 Recently, 33 we have shown that the ab initio calculations at the CASSCF/XMCQDPT2 (Extended Multi-Configuration Quasi-Degenerate 2 nd Order Perturbation Theory) 32 level of theory predict the spectroscopic parameters of the ground and some excited states of the KRb molecule with the high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The comprehensive set of non-relativistic PECs, permanent and transition dipole moments for the ground and excited states of KRb are available 11,[21][22][23][24][25] as well. The SOC effect has been included into ab initio calculations in Refs.…”
Section: Introductionmentioning
confidence: 99%